THE STUDENT OBSTACLES OF CREATIVE THINKING IN SOLVING MATHEMATICS PROBLEM - Purba, Elvira Magdalena (Jurnal Pendidikan Matematika (JUPITEK), 2020)
This study aims to describe the obstacles in creative thinking of class VIII students in solving class math problems about comparison. Creative thinking indicators consist of fluency, flexibility, and novelty. This type of research is qualitative descriptive. The subjects in this study consisted of 16 people who were students of SMPN1 and SMPN4 in Malang. The data collected in this study are student worksheets in solving problems of comparison and interview pieces. The results of this study found out of 16 there were 6 (37,5%) students who were not creative, 3 (18,75%) students were less creative, 2 (12,5%) students were quite creative, 3 (18,75%) students were creative people and 2 (12,5%) students were very creative. Obstacles from students who are not creative, less creative and quite creative are mistakes in understanding questions, easy self-satisfaction and lack of student experience